(untitled) (Human Factors in Design, 2023)
The objective of this study was to verify the influence of four models of assistive devices designed for tripod prehension, in the variables satisfaction with the device, satisfaction in the accomplishment and performance of the writing activity. This was a cross-sectional study composed of thirty university students, using two data collection instruments, QUEST 2.0 and COPM. The results indicated satisfaction with the adapters, as well as in their use for the writing activity. This study contributes to occupational therapists, educators, design and engineering in the development of new devices and the indication of adapters.